Source rock characterization of the Dingo Claystone, Barrow Sub-basin, Australia – Influence of contamination on geochemical analyses - Ummi Fayyadhah Binti Haji Talipudin; Mohamed Ragab Shalaby (Energy Geoscience)
An integrated study on source rock characterization and hydrocarbon generation potential modeling was conducted for the selected Dingo Claystone, Barrow Sub-basin, Australia. In this study, data were collected solely from two wells represented by the Bambra-1 and Bambra-2 wells. The collected data include those from bulk geochemical analyses of cuttings and sidewall cores sampled from the Late Jurassic Dingo Claystone. Geochemical data obtained from Rock-Eval pyrolysis and gas chromatography (GC) of extracted organic matter were integrated for source rock characterization and the construction of burial history and hydrocarbon generation in the Dingo Claystone. To improve the accuracy of thermal maturity estimations, only samples with S2 greater than 1 were considered due to potential issues with peak integration and uncertainties of Tmax determination in samples with lower S2 values. Furthermore, Rock-Eval data from the Bambra wells may be unreliable due to the contamination of cuttings and side-wall core (SWC) samples by drilling mud additives and natural hydrocarbons, which could impact the reliability of the data for determining thermal maturity. This study reveals that the Dingo Claystone Formation has total organic carbon (TOC) contents ranging from 0.66 % to 8.31 %. A poor to good hydrocarbon generation potential is indicated, with a production yield (PY=S1 + S2) ranging from 1.37 to 10.44 mg HC/g rock. Hydrogen index values vary between 42 and 226 mg HC/g TOC, confirming that the Dingo Claystone is dominantly kerogen Type III, with minor contributions from types II/III and IV. Thermal maturity ranges from immature to late mature and is mostly in the oil window. This is indicated by Tmax values of 398–462 °C and vitrinite reflectance (Ro, %) of 0.47–1.99. Some samples show suppressed Tmax and a higher production index, which is typical for samples affected by drilling fluids during drilling operations. Additionally, gas chromatography (GC) analyses are used to interpret the paleodepositional environment showing mixed input between marine and terrestrial origins of the source rocks. One-dimensional basin modeling for the Bambra-1 and Bambra-2 wells was carried out to evaluate the burial and thermal history of the formation. The transformation ratio suggests that hydrocarbon generation has not reached its peak and is still in an ongoing phase. An indication of hydrocarbon migration can be observed in this formation based on the transformation ratio. The effects of contamination warrant further investigation, as it could significantly impact maturity estimates and data reliability.